Cupid's book. Spokane. (E.F. Kiessling, 1929)
Cupid's book contains well selected recipes that can be relied upon, as they have all been passed on by expert culinaries, and much valuable information showing how the table should be set, table etiquette, time tables, weights and measures, temperature charts, meat cuts and their uses, and other valuable information that a housewife should know.